School Disciplinary Climate: Characteristics and Effects on Eighth Grade Achievement (Alberta Journal of Educational Research, 2004)
Seven dimensions of school disciplinary climate were identified based on a representative sample of grade 8 students in the United States. Within schools students varied considerably in their perceptions and experiences about discipline. The variation was related mainly to students' socioeconomic status (SES), sex, and ethnicity. There was a significant contextual effect of school mean SES on disciplinary climate, larger titan the individual effect of SES. Schools with primary or intermediate grades tended to have more favorable disciplinary climates titan either junior or senior high schools. School location had small effects on disciplinary climate. The disciplinary measure with the strongest relationship to academic achievement pertained to classroom disruption.